Using a collaborative approach to reduce falls in older people’s adult mental health wards in a local health board in Wales - Melanie Davies; Simon Williams; Louise Walker; Dolores Macchiavello; Zoe Williams; Paul Gimson; Kerstin Ackermann-Lloyd; Sophie Bassett; Christopher Bevan; Anna Brooks; Naomi Elias; Jessica Gapper; et al. (BMJ Open Quality)
Between April 2020 and March 2021, the number of fall-related emergency admissions in England for adults over 65 years was 1933 per 100 000 people. Adult patients in hospital may be at risk of falling for many reasons including a history of falls, being medically unwell, dementia or delirium, the effects of their treatment or medication, poor mobility, visual and other sensory impairments along with their general well-being. Research has shown that falls can be reduced by 20%–30% through multifactorial assessments and interventions. The aim of these assessments and interventions is to identify and treat underlying reasons for falls such as muscle weakness, cardiovascular problems, dementia, delirium, incontinence and medication. However, national audits have found low levels of implementation of these assessments and interventions in UK hospitals. As part of a new patient safety improvement initiative, a collaborative was developed to reduce the incidence of in-patient falls rate per 1000 bed days within five older adults’ mental health wards in a health board in Wales. The falls collaborative project has resulted in substantial improvements in care, including an increase of patients receiving lying and standing blood pressure assessment, medication review and delirium assessments. While reported falls rates stayed the same for the five wards, when each ward individually was factored in, we saw a reduction in two wards and estimated that the increase in falls for the remaining of three wards was related to a previous state of under-reporting, considering the numbers stayed levelled throughout the collaborative. The small reduction we saw was achieved without any extra support or allocated resources, and the ongoing staffing challenges all five wards experienced throughout the collaborative, all these improvements were received as a great success. The team was shortlisted for the National Health Service Wales Awards in the Safe Care category, something they took great pride in.